IMPLEMENTASI DIGITAL MARKETING MELALUI MEDIA SOSIAL TERHADAP MINAT BELI KONSUMEN DI U MART KABUPATEN SIDENRENG RAPPANG - Muhammad Ikram; Pratiwi Ramlan; Rahman Yakub; Haslindah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Social media has become one of the main tools in an effective modern marketing strategy, especially for local businesses like U Mart. This study aims to analyze the implementation of digital marketing through social media at U Mart in Sidenreng Rappang Regency and its influence on consumer buying interest. Through a quantitative approach, this study explores how digital marketing strategies are designed, implemented, and received by consumers, as well as identifying the factors that influence their success. Data collection techniques were carried out through observation, questionnaires, and documentation/literature studies. The data analysis technique used is descriptive quantitative analysis with the help of the SPSS 21 program. The results of the study show that the implementation of digital marketing through Facebook at U Mart is in the high category, with an average respondent response of 83.3%. Meanwhile, consumer buying interest is also high with an average of 84.3%. The regression test shows a significance value of 0.000 (< 0.05), which means there is a positive and significant influence between digital marketing strategies through social media and consumer buying interest at U Mart.